2021
DOI: 10.3390/bios11080286
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Anticancer Drug Sensitivity Sensing through Single-Cell Raman Spectroscopy

Abstract: Traditional in vitro anticancer drug sensitivity testing at the population level suffers from lengthy procedures and high false positive rates. To overcome these defects, we built a confocal Raman microscopy sensing system and proposed a single-cell approach via Raman-deuterium isotope probing (Raman-DIP) as a rapid and reliable in vitro drug efficacy evaluation method. Raman-DIP detected the incorporation of deuterium into the cell, which correlated with the metabolic activity of the cell. The human non-small… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…Raman spectroscopy (RS) is one of the most popular optical methods used to measure living sample viability [ 62 , 63 ]. Optical spectroscopy detects inelastic photon scattering caused by vibrational bonds in objects [ 64 ].…”
Section: Living Sample Viability Measurement Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Raman spectroscopy (RS) is one of the most popular optical methods used to measure living sample viability [ 62 , 63 ]. Optical spectroscopy detects inelastic photon scattering caused by vibrational bonds in objects [ 64 ].…”
Section: Living Sample Viability Measurement Methodsmentioning
confidence: 99%
“…The automatic development of RS algorithms involves analyzing vast quantities of data and the creation of a reliable and comprehensive database for machine learning [ 70 ] so as to increase the speed and reliability of testing. RS was recently combined with deuterium labeling, and the findings indicated that this novel RS detection technology might be used to identify cancer cells at the single-cell level [ 63 ]. RS’s challenges include the weak Raman signal [ 71 ] and light scattering [ 72 ], which reduce the method’s sensitivity.…”
Section: Living Sample Viability Measurement Methodsmentioning
confidence: 99%
“…For instance, although paclitaxel (PTX) is one of the most commonly used first-line chemotherapeutic drugs for treating a variety of tumors [ 4 ], its clinical efficacy in the treatment of breast cancer is dramatically affected by its drug resistance and severe side effects [ 5 ]. The underlying reason is that, in the preclinical trials of a drug development, the two-dimensions (2D) and three-dimensions (3D) cell models of in vitro cell experiments and the animal models of in vivo animal experiments are significantly distinctive from human models [ 6 , 7 ] and, furthermore, these preclinical trials ignore the heterogeneity among individual patients [ 8 ]. In the clinical practice, anticancer drug susceptibility testing is often conducted before chemotherapy treatment, which can provide a reference for clinicians to make personalized medication decisions and seek precision medicine for individual patients so as to improve the clinical outcomes of chemotherapy [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…The ex vivo tests performed on primary patient-derived tumor samples, such as xenograft models [ 13 ] and tumor tissue slices [ 14 ], are limited by their drawbacks including time-consuming sample preparation, low throughput, and low success rate of establishing a xenograft model [ 15 ]. The traditional in vitro drug susceptibility testing method on 2D or 3D culture models at cell population level suffers from insufficient number of cells [ 16 ], lengthy procedures [ 8 ] and high false positive rates due to the involvement of extra toxic reagents [ 8 ], and fails to detect heterogeneities in the cell population [ 8 ]. Therefore, it is essential to develop an in vitro anticancer drug susceptibility testing method that can accurately evaluate the susceptibility of individual patients to anticancer drugs with less toxic or non-toxic compounds and short testing procedure, and reflect the tumor heterogeneity on single-cell level.…”
Section: Introductionmentioning
confidence: 99%
“…Technical advances (3-dimentional cell culture, organoids, genetic-modified cells and others. [15][16][17][18][19] 2. High-throughput and miniature screening.…”
mentioning
confidence: 99%